تداول المعلومات عبر بوابة الحکومة المصریة :دراسة تحلیلیة - د. اسماء صلاح على (المجلة الدولية لعلوم المكتبات والمعلومات)
Information plays an important role in the development of societies. andhelp to increase the toll cultural and scientific knowledge of the individual, andopens his doors at various scientific fields of knowledge, information andprepare the way for innovation and creativity in life as it is for the advancementand construction of advanced societies, leads circulation of information in thecommunity to support the government to achieve development goals and enablecitizens to make decisions that the evolution of their lives,the survey aims to highlight the importance of the exchange of informationand its role in achieving sustainable development of the communities, and tostudy the circulation of information Law and presentation of international andlocal experiences, in addition to the analysis of the Lyon declaration ofcirculation information and how to take advantage of it in support of the activitiessustainable development, and the study will address the Egyptian governmentportal site description, analysis and find out how to apply the law of thecirculation of information and its role in the sustainable development of theEgyptian society.In order to the study will depend on descriptive and analytical method,descriptive and analytical approach that deals with the collection, informationand facts, analysis and interpretation. The axes of the study are1. the circulation of information: the concept and importance and its role inachieving sustainable development of the society2. Information law and most famous international experience to apply this3. law Lyon currently circulation information and its role in achievingsustainable development4. Description and analysis of the Egyptian government portal site on theInternet and the extent achievable for the development of society and theextent of the law to achieve the circulation of information.